PENERAPAN LITERASI BERBASIS AL-QUR’AN DALAM MENINGKATKAN MOTIVASI BERAGAMA SISWA DI MADRASAH IBTIDAIAH - Nadhrioh, Syifaun (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam Universitas Islam Malang, 2022)
Al-Qur'an literacy needs to be taught to children early, so they have solid and good religious knowledge and understanding. This article aims to find patterns of applying Al-Qur'an literacy in increasing students' religious motivation at Madrasah Ibtida'iah Bustanul Ulum Tulungagung. The type and approach in this research are qualitative with a phenomenological basis. Primary data sources who became key research informants were the Head of the School, the Deputy Head of the Curriculum Section, and the teachers. The collected data were analyzed using qualitative interactive model techniques, condensing data, displaying data, and drawing conclusions. The study results concluded that the implementation of al-Qur'an literacy in Madrasah Ibtida'iah Bustanul Ulum Tulungagung had been scheduled from Monday to Thursday through learning to read, listening for 35 minutes before class begins by utilizing various applications such as the Madrasah Ibtida'iah live youtube channel Bustanul Ulum Tulungagung. In carrying out the Al-Qur'an literacy schedule, Madrasah Ibtida'iah Bustanul Ulum Tulungagung prepared a companion team that had received a literacy companion certificate from the ministry of religion